Hematological Toxicity in Carcinoma Cervix Patients Undergoing Concurrent Chemo Radiation Therapy or Radiation Therapy alone in a Tertiary Hospital of North East India: A Prospective Study - Baruah, Chiranjiv; Paul, Trishan; Sarma, Biswajit; Deka, Kankan Jyoti; Patowory, Partha Pratim (Asian Pacific Journal of Cancer Care, 2022)
Introduction: The current standard of treatment for locally advanced cancer of cervix is cisplatin based concurrent chemo radiation therapy followed by brachytherapy. Concurrent chemo radiotherapy causes acute hematological toxicities, which in turn leads to prolongation of therapy. Objective: The main purpose of our study, was to analyze the acute hematological toxicity in cervical cancer patients undergoing radiation or chemo radiation therapy. Materials and Methods: This is a hospital based observational study done at department of Radiation Oncology, Assam medical college and hospital. All the biopsy proven cervical cancer patients attending the department, within the study period from September 2020 to May 2021 are included in the study. Results: Out of 26 patients in the study sample, grade 1 hematologicaltoxicity is seen in 2 patients (7.5%), grade 2 hematological toxicity seen in 20 patients (77%), grade 3 hematological toxicities in 4 patients (15.5%) and none of the patients developed grade 4 nor grade 5 hematological toxicity or any other life threatening complications. Conclusion: Hematological toxicity is more common with conventional external beam therapy in locally advanced carcinoma cervix patients. Compared to conventional external beam radiotherapy and 3DCRT, patients undergoing treatment with IMRT experiences significantly less acute grade ≥2 hematological toxicities.